Analisis Psikologi Humanistik dalam Novel Buku Besar Peminum Kopi Karya Andrea Hirata dan Pemanfaatannya sebagai Alternatif Materi Pembelajaran Sastra di SMA - Arzeti Alivia Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to describe Abraham Maslow's hierarchy of needs in the novel The Big Book of Coffee Drinkers by Andrea Hirata. This research is a qualitative descriptive research with a humanistic psychology approach. The data collection technique used in this research is a documentation technique. The data source in this research is the novel The Big Book of Coffee Drinkers by Andrea Hirata and other supporting documents. The data in this research are in the form of words, sentences, paragraphs and dialogue which indicate the existence of elements of humanistic psychology, Abraham Maslow's hierarchy of needs theory in the novel The Big Book of Coffee Drinkers by Andrea Hirata. Data analysis techniques in this research include data reduction, data presentation, data interpretation, as well as drawing conclusions and verification. The research results show that needs are interconnected and human needs in the present can be influenced by human needs in the past. This is proven by the character Nong who distorts his past experiences regarding the need for love for the opposite sex which is not well realized into a medium for self-actualization. The results of this research can also be used as an alternative literature learning material in class XI high schools.
This research aims to describe Abraham Maslow's hierarchy of needs in the novel The Big Book of Coffee Drinkers by Andrea Hirata. This research is a qualitative descriptive research with a humanistic psychology approach. The data collection technique used in this research is a documentation technique. The data source in this research is the novel The Big Book of Coffee Drinkers by Andrea Hirata and other supporting documents. The data in this research are in the form of words, sentences, paragraphs and dialogue which indicate the existence of elements of humanistic psychology, Abraham Maslow's hierarchy of needs theory in the novel The Big Book of Coffee Drinkers by Andrea Hirata. Data analysis techniques in this research include data reduction, data presentation, data interpretation, as well as drawing conclusions and verification. The research results show that needs are interconnected and human needs in the present can be influenced by human needs in the past. This is proven by the character Nong who distorts his past experiences regarding the need for love for the opposite sex which is not well realized into a medium for self-actualization. The results of this research can also be used as an alternative literature learning material in class XI high schools.
Keywords: Buku Besar Peminum Kopi; Humanistic Psychology; Hierarcy Need